Evaluación de los factores ambientales del plan de cierre de mina en la unidad minera aurifera anabi. - Vera Gutiérrez, Sheyla Milagritos (2014)
An evaluation of environmental factors was performed for the progressive closure plan of the Mining unit Aurífera Anabi These are the environmental factors evaluated: (Water, Soil, Air, Flora, Fauna and Landscape Environment). The results showed that the progress of the activities of environmental factors captured in the mine closure plan (MCP) are met on a schedule during the years 2012 and 2013, it is clarified that there was quarters which real progress was better that theoretical, and vice versa advance, this detail is justified giving knowledge that there is amending of the PCM that was submitted to the competent authority for review and approval respective. For the environmental factors were determinated the percentages of advances total real until the year 2013 in comparison with the percentages of advances total theoretical until the year 2013, having as result for the water environmental factor values of 44.98%, compared to 60% . In relation to the soil environmental factor, this one showed the values of 63.89 %, in comparison of 57.89 %. As for values air environmental factor, it reached 77.77% compared to 22.22%. Regarding environmental factors flora and fauna, presented the values 77.77% compared to 22.22%. And finally, landscape's environmental factor values presented 77.77% compared to 66.67%.